Sistem Pendukung Keputusan Penerima Beasiswa Di SMKN 1 Cikarang Utara Dengan Metode Analitycal Hierarchy Process - Naya, Candra; Siswandi, Arif (Jurnal SIGMA, 2023)
The selection process in determining the scholarship recipients still experiencing problems. In the field was found less like the scholarships are caused by a system that is still a conventional or manual. In addition, decision makers can’t see these criteria in a scholarship. In computer science, there is a system that can help decision makers to address the problem of the nature of the spring the structure or lack of structure the system of supporting the decision. In Support System's decision there are various methods of one of them is the method of Analytical Hierarchy Process (AHP) who was found by Thomas L.Saaty. AHP own can help in determining the priorities of some criteria with analysis, the comparison of pairs of each criteria that have been found. By looking at problems in decision-making in the selection of scholarship recipients, a support system decisions by using the method of AHP is right to use in helping to make a decision to determine the recipient of the scholarships. It is hoped that results in this research may help decision makers in determining the scholarship recipients. Keyword: Selection, Computer Science, Support System Decision, Method AHP